STUDENT MOTIVATION AND LEARNING OUTCOMES THROUGH ONLINE FLIPPED CLASSROOM BASED ON STUDENT SELF-REGULATION IN COASTAL AREAS - Muali, Chusnul; Aisyah, Nur; Faizah, Nurul (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
Most learning motivation research focuses on students' performance with various abilities and skills and still needs to integrate constructive learning technology tools. Therefore, this study answers research questions about differences in stu-dent motivation and learning outcomes using the online flipped classroom based on differences in students' self-regulatory levels. Data was obtained from 108 students in coastal area schools, who were divided into two groups. Students' self-regulative abilities are measured using a four-point Likert scale, and learning outcomes are obtained from multiple-choice questions. The data collection in-strument used resulted from the developing of The Motivated Strategies for Learning Questionnaire (MSLQ). The hypothesis was tested using multivariate analysis of variance to find answers to research questions. The results of this study show higher levels of motivation and learning outcomes in the online flipped classroom group. Furthermore, the research results show the influence of student self-regulation on student motivation and learning outcomes.